Through a glass darkly: Using a reflecting team approach in the development of supervisory practice. (September 2019) - Smith, Margaret
Foulkes placed working with countertransference and parallel process as central to group supervision. This article offers a model for developing supervisory skills in recognizing and making use of countertransference and parallel process in group supervision. It adds two perspectives: firstly it draws on Alfred Lorenzer's concept of 'scenic understanding', a method of identifying social and cultural triggers from the past that cause patients' problems in the present but which are outside of conscious awareness. Secondly, it adapts a reflecting team approach developed by Anderson and Prest for use in training supervisors of groups. In the following model of reflecting team supervision it is the therapist's 'scenes', triggered and evoked by a patient or therapy group that are presented. The supervision group responds by offering their associations and emotional responses, and this is observed by a reflecting team. They then change places and the supervision group watches the reflecting team offer their observations and hypotheses. In the final stage of the process, the two groups meet together to share their learning and reflect on the experience. This approach is illustrated with vignettes, and highlights some of the benefits.